Awake tracheal intubation with the ProVu™ video stylet: a case series. Issue 1 (29th March 2021) - Harrison, S‐L.; Ahmad, I.; Elwen, F.; Curtis, A.; Dua, G.; Surda, P.; Johnstone, C.
Summary: Management of the difficult airway is integral to peri‐operative practice. The development of devices to simplify airway handling are changing our approach to tracheal intubation. We report a case series of three patients who underwent awake tracheal intubation with the ProVu™ video stylet (Flexicare Medical Ltd, Mountain Ash, UK). All three patients had predicted difficult airways, including: limited mouth opening secondary to radiotherapy; previous exenteration, hemi‐maxillectomy and scapular free flap formation; and cervical fixation. Awake tracheal intubation was performed successfully in all three cases, with no complications reported. This is the first reported case series of the ProVu™ video stylet as an awake tracheal intubation device. The benefits and limitations of this video stylet are discussed.